Diskursus Digital tentang Antrean Masuk SD Muhammadiyah Sapen di Instagram: Analisis Korpus terhadap Pembentukan Persepsi Publik - Hidayanto, Rizky; Junaedi, Fajar (Universitas Muhammdiyah Yogyakarta, 2026)
This study aims to analyze how public discourse on social media shapes perceptions of the quality and reputation of SD Muhammadiyah Sapen Yogyakarta. The dataset consists of 1,192 user comments collected from Instagram posts by @folkyogya and @gnfi. A corpus-based text analysis approach was employed using Voyant Tools, including Cirrus, Trends, Bubblelines, Mandala, ScatterPlot (t-SNE), and TermsBerry, to examine lexical patterns, semantic relationships, and discourse structures. The findings reveal that public discourse is constructed in a multidimensional manner through dominant keywords, shifting thematic focus, and clustered discourse patterns reflecting complex user interactions. Perceptions of the school are shaped by three main dimensions: institutional identity, child-oriented concerns, and competition for educational access. The results demonstrate that institutional reputation is not solely formed through formal communication, but through participatory culture, electronic word of mouth (e-WOM), and virality, which accelerate the dissemination and reproduction of meaning in digital spaces. This study offers a theoretical contribution by integrating these three concepts into a unified framework of digital discourse analysis, and a methodological contribution through the application of corpus-based analysis in social media communication research.